1996
DOI: 10.1182/blood.v87.1.256.256
|View full text |Cite
|
Sign up to set email alerts
|

Chlorodeoxyadenosine and arabinosylcytosine in patients with acute myelogenous leukemia: pharmacokinetic, pharmacodynamic, and molecular interactions

Abstract: The effectiveness of arabinosylcytosine (ara-C) for the treatment of acute myelogenous leukemia (AML) depends on the formation of its active metabolite, the triphosphate of ara-C (ara-CTP). Using biochemical modulation strategies to increase the accumulation of ara-CTP in leukemia blasts, a clinical protocol was designed combining 2- chlorodeoxyadenosine (CdA), an inhibitor of ribonucleotide reductase, and ara-C for adults with AML. The protocol stipulated an infusion of 1 g/m2 of ara-C over 2 hours on day 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(39 citation statements)
references
References 28 publications
0
38
1
Order By: Relevance
“…dFdC showed a close resemblance to Ara-C but with major quantitative and qualitative differences from the latter compound with regard to biological and clinical effects (1,5). Several authors have demonstrated that combined therapy consisting of 2-CdA and Ara-C was more effective than monotherapy with the drugs used separately (3,29). Our previous experiments had also con®rmed that the most effective treatment schedule was Ara-C given before 2-CdA, and that 2-CdA can potentiate the antineoplastic activity of Ara-C (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dFdC showed a close resemblance to Ara-C but with major quantitative and qualitative differences from the latter compound with regard to biological and clinical effects (1,5). Several authors have demonstrated that combined therapy consisting of 2-CdA and Ara-C was more effective than monotherapy with the drugs used separately (3,29). Our previous experiments had also con®rmed that the most effective treatment schedule was Ara-C given before 2-CdA, and that 2-CdA can potentiate the antineoplastic activity of Ara-C (30).…”
Section: Discussionmentioning
confidence: 99%
“…Ara-C is one of the most effective agents for the treatment of acute myeloid leukemias (AML). It has also been successfully applied in combined chemotherapy with purine analogs to the treatment of chronic myeloid leukemia (CML) in blast crisis (3,4). The remarkable activity of dFdC against human leukemic cell lines and solid tumors, which is more impressive than that of Ara-C, stimulated interest in clinical trials (5).…”
mentioning
confidence: 99%
“…A combination of FA, Ara-C, and G-CSF (FLAG regimen) has been used in the treatment of refractory and relapsed AML and poor prognosis myelodysplastic syndromes (MDS), with CR rates of between 30% and 80% reported (18)(19)(20)(21)(22). Recent studies have shown that another purine analog, cladribine (2-CdA), is also able to enhance Ara-CTP accumulation in leukemic blasts (23,24). Moreover, Chow et al reported that the combination of 2-Cda with Ara-C exhibited synergistic effect on inhibition of myeloid leukemic cell proliferation, induction of apoptosis as well as on disruption of mitochondrial membrane potential.…”
mentioning
confidence: 99%
“…The end result is cytarabine triphosphate (ara-CTP), the active form of the drug. Upon discovery that fludarabine was able to augment ara-CTP in CLL [22] and later AML [23], Gandhi et al investigated the interplay between CdA and ara-C, given CdA is a more potent ribonucleotide reductase inhibitor than fludarabine [24]. Nine patients with AML received a single dose of ara-C 1 g/m 2 on day 1 followed by CdA 12 mg/m 2 /day on days 2 to 6.…”
Section: Pharmacologymentioning
confidence: 99%